Problems of Lithuanian mathematical olympiad’07 - Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2021)
The problems of the Lithuanian school olympiad-2007 are presented and solutions are given.
Keywords: mathematical olympiads; problems solving; functional equation